Minat Mahasiswa Menabung di Bank Mini Syariah Sekolah Tinggi Agama Islam Auliaurrasyidin Tembilahan - Desi Salvia; Seri Yanti Siagian (AL-Muqayyad, 2022)
This research is motivated by the number of Islamic economics students as many as 216 or about 57% for the 2017-2020 class who save at Mini Syariah Banks, and around 43% who have not saved at Mini Syariah Banks. To find out the interest of Islamic Economics Students in saving at Mini Syariah Banks, the researchers distributed questionnaires to Islamic economics students to find out the students' interest in Islamic Mini Banks. The purpose of this study was to determine the interest in saving students of the Islamic economics study program at the Mini Syariah Bank, Auliaurrasyidin Tembilahan Islamic High School. This research is a qualitative descriptive study. The results of the questionnaire research show that the interest of students of the Islamic Economics Study Program in Savings at Mini Syariah Banks, Islamic High School Auliaurrasyidin Tembilahan is in the percentage of "87.6%" with the category of "Very Good". Thus, it can be concluded that the interest of students of the Islamic economics study program in saving in Islamic mini banks is in the good category.